Recommendations related to the analytical equivalence assessment of gene panel testing. Issue 10 (19th August 2022) - Nagai, Sumimasa; Nishihara, Hiroshi; Suzuki, Takayoshi; Nishio, Kazuto; Taniguchi, Hiroya; Tsuchihara, Katsuya; Nakamura, Kohei; Takamatsu, Reika; Ueno, Toshihide; Aburatani, Hiroyuki; Kohno, Takashi; Kohsaka, Shinji
Abstract: Advances in cancer genome care over the past few years have included the development of gene panel testing for various biomarkers. This article summarizes issues and provides recommendations related to analytical performance evaluations for new oncology gene panels. The scope of these recommendations includes comprehensive genomic profiling assays related to gene panel testing that uses histological or serum specimens to detect gene mutations. As a research project of the Japan Agency for Medical Research and Development Research on Regulatory Science of Pharmaceuticals and Medical Devices, we convened the working group committee that consisted of more than 30 experts from academia, industry, and government. We have discussed the points that should be considered to allow maximal simplification of assessments using clinical specimens in evaluating accuracy and limit of detection in equivalence and analytical performance for 3 years. We provide recommendations specific to each type of gene mutation as well as to reference standards or specimens used for evaluations. In addition, in order to facilitate the discussion on the analytical performance of gene panel tests by multidisciplinary tumor boards of hospitals, the present recommendations also describe the items that companies are expected to provide information on in their packaging inserts and reports, and the items that are expected to be discussed by multidisciplinary tumor boards. Our working group document will be important for participants in multidisciplinary tumor boards, including medical oncologists and genome scientists, and developers of gene panels not only in Japan but also in other countries.